HAK ASASI MANUSIA DALAM PERSPEKTIF HUKUM ISLAM - Hamdan, Hamdan (TASÂMUH, 2016)
Human rights were declared by United Nation in 1948. Human rights become a reference for international world and influence all aspect relations and contemporarily-international law. However, interpretation and implementation of human rights in national scope are not as smooth as its acceptance. Collision between culture and local law and universal human rights cannot be avoided. Islamic law is the product of Syariah that is applied in all over Muslim countries in which they are also United Nation member. Is there a collision between international law of human rights and Islamic law, then how to solve it. This is a statement that has to be answered thoroughly in those both perspectives. Dialogical approach gives the most satisfactory solution. Through the doctrine of marginal appreciation in one side and benefit in another side, both are entrance for other cases for opening dialogues in order to achieve collective understanding about human rights. The positive effect for Islamic law is Fiqih that is like to regain its spirit and the benefit is not merely jargons.